Leveraging genetic association data to investigate the polygenic architecture of human traits and diseases - Chan, Ying Leong (Harvard University, 2014)
Many human traits and diseases have a polygenic architecture, where phenotype is partially determined by variation in many genes. These complex traits or diseases can be highly heritable and genome-wide association studies (GWAS) have been relatively successful in the identification of associated variants. However, these variants typically do not account for most of the heritability and thus, the genetic architecture remains uncertain.